PENDIDIKAN AGAMA ISLAM BERWAWASAN KEARIFAN LINGKUNGAN DI SEKOLAH DASAR: Dasar, Signifikansi dan Implementasi - Syamsul Kurniawan (Journal of Research and Thought on Islamic Education, 2019)
If we agreed that human beings and their thoughts are the products of an educational process that they obtain, it can be said that the nature and behavior of humans that damage the environment are caused by the education that they got less optimal in strengthenig environmental wisdom. Because of that the lesson of Islamic Education should be able to be optimally given early for children, such as children of primary school. Environmental-oriented of Islamic Education needs to be given to students such as teaching them about the importance of caring for and preserving the environment and its functions. The focus of this paper is conceptual discussion of environmental oriented Islamic education in elementary schools concerning the basis, significance and implementation. Problem that want to be revealed through this paper: First, in Islam, what underlies the importance of Islamic education with environmental wisdom given to elementary school students? Second, why does Islam strongly emphasize the importance of strengthening environmental wisdom through Islamic education? Third, how should Islamic education with environmental wisdom given to elementary school students?